Aligning tourism's socio-economic impact with the United Nations' sustainable development goals. (July 2021) - Kronenberg, Kai; Fuchs, Matthias
Abstract: Socio-economic sustainability for tourism workers does not play a prominent role in contemporary tourism economic impact studies. Rather, to promote economic growth paradigms, the focus lies on aggregated employment and income effects. To better understand tourism's contribution to decent work and reduced inequalities (Sustainable Development Goals 8 and 10, respectively), our study assesses tourism's socio-economic impact by focussing on meso-level perspectives from major tourism institutions that are complemented with macro-level results gained through an occupation-based Input-Output model. Although income inequalities across tourism occupations remain relatively low, income inequalities over a period of nine years have increased. Tourism employees continue to work in precarious occupations due to limited training and career opportunities. Employers demand skilled vocational professions and provide non-monetary benefits; however, respective salaries remain average. Altogether, tourism contributes to Sustainable Development Goals 8 and 10 only moderately, and regional tourism institutions need to continue their development strategies for greater sustainability. Highlights: Institutional perspectives help to better understand economic impacts. Tourism plays a crucial role for generating and maintaining regional employment. However, income inequality is increasing due to higher shares of low-paid positions. Majority of tourism workers remain in precarious employment without education. Institutional initiatives are important for socio-economic sustainability.